Teen Ink : what matters - Meyer, Stephanie H., 1946-; Meyer, John, 1943-; Veljkovic, Peggy, 1967- (Deerfield Beach, Fla. : Health Communications, 2003)
A collection of stories and poems by teenage writers, arranged in such categories as "Challenging matters," "Family matters," and "World matters."
What matters -- Challenging matters -- Family matters -- World matters -- Life matters -- I matter -- Heroes matter -- Younger matters -- Moments matter.
Keywords: Adolescence -- Literary collections; Youths' writings, American; Youths' writings